Dengue virus – elicited tryptase induces endothelial permeability and shock - Rathore, Abhay P. S. (2020)
Dengue virus (DENV) infection causes a characteristic pathology in humans involving dysregulation of the vascular system. In some patients with dengue hemorrhagic fever (DHF), vascular pathology can become severe, resulting in extensive microvascular permeability and plasma leakage into tissues and organs. Mast cells (MCs), which line blood vessels and regulate vascular function, are able to detect DENV in vivo and promote vascular leakage. Here, we showed that an MC-derived protease, tryptase, is consequential for promoting vascular permeability during DENV infection through inducing breakdown of endothelial cell tight junctions. Injected tryptase alone was sufficient to induce plasma loss from the circulation and hypovolemic shock in animals. A potent tryptase inhibitor, nafamostat mesylate, blocked DENV-induced vascular leakage in vivo. Importantly, in 2 independent human dengue cohorts, tryptase levels correlated with the grade of DHF severity. This study defines an immune mechanism by which DENV can induce vascular pathology and shock.